Microphysiological Drug‐Testing Platform for Identifying Responses to Prodrug Treatment in Primary Leukemia. Issue 6 (27th January 2023) - Gökçe, Furkan; Kaestli, Alicia; Lohasz, Christian; de Geus, Martina; Kaltenbach, Hans‐Michael; Renggli, Kasper; Bornhauser, Beat; Hierlemann, Andreas; Modena, Mario
Abstract: Despite increasing survival rates of pediatric leukemia patients over the past decades, the outcome of some leukemia subtypes has remained dismal. Drug sensitivity and resistance testing on patient‐derived leukemia samples provide important information to tailor treatments for high‐risk patients. However, currently used well‐based drug screening platforms have limitations in predicting the effects of prodrugs, a class of therapeutics that require metabolic activation to become effective. To address this issue, a microphysiological drug‐testing platform is developed that enables co‐culturing of patient‐derived leukemia cells, human bone marrow mesenchymal stromal cells, and human liver microtissues within the same microfluidic platform. This platform also enables to control the physical interaction between the diverse cell types. Herein, it is made possible to recapitulate hepatic prodrug activation of ifosfamide in their platform, which is very difficult in traditional well‐based assays. By testing the susceptibility of primary patient‐derived leukemia samples to the prodrug ifosfamide, sample‐specific sensitivities to ifosfamide in primary leukemia samples are identified. The microfluidic platform is found to enable the recapitulation of physiologically relevant conditions and the testing of prodrugs including short‐lived and unstable metabolites. The platform holds great potential for clinical translation and precision chemotherapy selection. Abstract : The authors present a microphysiological platform to recapitulate the metabolic activation of prodrugs in vitro for personalized drug screening against leukemia. The platform enables the co‐culture of primary leukemia cells, stromal cells, and liver microtissues in a microfluidic network. Sample‐specific sensitivities to short‐lived ifosfamide metabolites are identified in primary leukemia samples, which cannot be easily assessed in existing screening assays.